The Current State of Studies in the Problem of Forming the Professional Identity of Future IT Specialists - Крашеніннік, Ірина; Kachur, Artem (Educological discourse, 2024)
The article examines professional identity - a psychological formation that is important for ensuring the quality of life, mental well-being, professional self-realization and social success of an individual. The purpose of this material is to study scientific views on the professional identity of an individual and to determine the main features of this phenomenon, which are significant for the formation of the professional identity of future IT specialists in the process of professional training in institutions of higher education. For its implementation, the selection of scientific sources, theoretical analysis of scientific approaches to the problem of professional identity, generalization, systematization of theoretical material, formulation of conclusions were used. The article presents the results of the analysis of scientific works of Ukrainian researchers. It is shown that the main attention is paid to the formation of the professional identity of the individual in the professions of the "human-human" type, the peculiarities of its formation within the boundaries of the "human-technical" professions have not been sufficiently studied. A number of definitions of professional identity, views on its structure, influencing factors and indicators of formation are given. Scientists emphasize that professional identity has personal and social components, is formed under the influence of many factors in the process of communicative, educational, professional-practical and reflective activities. The conducted analysis made it possible to make some theoretical assumptions. In particular, the professional identity of a future IT specialist can be considered as a psychological formation that combines cognitive, motivational, behavioral and value characteristics of an individual, ensures his professional self-determination and professional self-realization in the process of training and further professional activities in the field of information technologies. It includes self-awareness as an IT specialist capable of effectively performing production tasks and as a member of a professional IT community. In the structure of the professional identity of the future IT specialist, the following components can be distinguished: cognitive, motivational-value, emotional-volitional, action-oriented, reflective. The formation of the professional identity of an IT specialist takes place in the course of professional training in educational programs of relevant specialties, and further development in the process of professional activity.